False alarms in damage detection approaches - Bueno, Douglas Domingues [UNESP]; Marqui, Clayton Rodrigo [UNESP]; Santos, Rodrigo Borges [UNESP]; Da Silva, Samuel; Junior, Vicente Lopes [UNESP] (My University, 2008)
Structural Health Monitoring (SHM) denotes a system with the ability to detect and interpret adverse changes in structures in order to improve reliability and reduce life-cycle costs. The greatest challenge for designing a SHM system is knowing what changes to look for and how to classify them. Different approaches for SHM have been proposed for damage identification, each one with advantages and drawbacks. This paper presents a methodology for improvement in vibration signal analysis using statistics information involving the probability density. Generally, the presence of noises in input and output signals results in false alarms, then, it is important that the methodology can minimize this problem. In this paper, the proposed approach is experimentally tested in a flexible plate using a piezoelectric (PZT) actuator to provide the disturbance.
Keywords: Damage detection; False alarms; Probability density; PZT actuator; Time series; Damage Identification; Detection approach; Flexible plates; Input and outputs; Lifecycle costs; Probability densities; PZT; Vibration signal analysis; Actuators; Alarm systems; Errors; Exhibitions; Structural dynamics